Piloting a National Programme for the Digitization of Medieval Manuscripts in Germany - Claudia Fabian; Carolin Schreiber (Liber Quarterly: The Journal of European Research Libraries, 2014)
An initiative to develop a concerted national programme for the digitization of medieval manuscripts in Germany was launched by five German manuscript centres in January 2013. This new proposal aims at the development of a master plan for the digitization of nearly all surviving medieval manuscripts in Germany and at the establishment of a new funding programme of the DFG (German Research Foundation), the largest research funding organization in Germany.